2013
DOI: 10.1177/1087057113486000
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Colorimetric and a Fluorescence Phosphatase-Inhibitor Assay Suitable for Drug Discovery Approaches

Abstract: Protein phosphatases (PP) are interesting drug targets. However, their ubiquitous presence and involvement in different, partially opposing signal pathways suggest that specificity may be achieved rather by targeting their interaction with subunits determining substrate specificity than the enzyme itself. An interesting subunit is phosphatase inhibitor-1 (I-1), which, in its protein kinase A–phosphorylated form (I-1P), inhibits the catalytic subunit of type 1 phosphatase (PP1c). In the current study, we establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…The necessity for such a prolonged incubation indicated that Rtr1 can dephosphorylate p NPP but with very low activity. Therefore, we switched to a more sensitive assay that uses the fluorescent compound DiFMUP, which is 500 times more sensitive than the p NPP assay (16) and has been used to assay the activity of K. lactis Rtr1 (10). …”
Section: Resultsmentioning
confidence: 99%
“…The necessity for such a prolonged incubation indicated that Rtr1 can dephosphorylate p NPP but with very low activity. Therefore, we switched to a more sensitive assay that uses the fluorescent compound DiFMUP, which is 500 times more sensitive than the p NPP assay (16) and has been used to assay the activity of K. lactis Rtr1 (10). …”
Section: Resultsmentioning
confidence: 99%
“…The K M for PRLs was determined separately (PRL-3 = 21 μM, PRL-2 and PRL-1 = 24 μM). The K M for PP1 (91 μM) and for PP2A (100 μM) was taken from the literature [ 38 , 39 ]. Protein concentrations are 50 nM for all PRLs and 2 mU for PP1 and 0.05 U for PP2A (see the Experimental Procedures ).…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether it is the bulkiness of Bpa or the fact that it is an unnatural amino acid that accounts for the cellular stability it imparts to PDP3, we synthesized PDPs that contained the small amino acids d ‐alanine ( d al ), β‐alanine ( βal ), or bulky 2‐naphthylalanine ( Nal ). First, we tested if these PDPs disrupted in vitro the interaction of PP1 with the regulatory protein I2 to liberate PP1, such that it could dephosphorylate the fluorogenic substrate 6,8‐difluoro‐4‐methylumbelliferyl phosphate (DiFMUP) . The results show that all peptides maintain in vitro activity in a similar potency range, with PDP3 showing the highest EC 50 (Table and Figure S1 in the Supporting Information).…”
Section: Pdps Used For This Study and Their Ec50 Values For Deinhibitmentioning
confidence: 99%